Motor performance of preschool children - Karina Słonka; Manuela Dyas; Tadeusz Słonka; Tomasz Szurmik (Kazimierz Wielki University, 2017)
Introduction: Pre‑school age is a period of intensive development when children shape their posture, habits and motor memory. Movement is child's physiological need.  Motive activity supports not only physical development, but also psychical, intellectual and social.   Aim: The aim of the study is to assess motor ability in preschool children from the city of Opole and District Dobrzeń Wielki. Materials and methods: The research involved 228 children, aged 5 and 6. The method used in the study, was Wroclaw motor performance test for preschool children. Test was conducted within the framework of Kindergartner's Spartakiad organized cyclic by the Technical University of Opole. Results: Analysis of the outcomes has proven, that with the age there is a systematic improvement of the results in each fitness trial, however calculated on the points, level motor performance of preschool children is unsatisfactory. Comparing the results obtained in individual tests of fitness to the norms, showing a decrease in the level of motor skills with children's age. Comparing of the results with the research carried in the 1980s led us to conclusion that the level of motor skills of rural children has improved. Examined 5 - years-old showed a higher level of motor performance than examined their peers in the 1980s.